Occurrence of the birds of the Middle Volga Region (South-East of the European part of Russia) - Anastasia Klenina (Pensoft Publishers, 2021)
Birds are the most numerous and widespread group of higher vertebrates. Due to the peculiarities of their biology, birds play an important role in nature and in human life.Ornithological studies described in this publication were conducted in seven regions of the Middle Volga Region (Chuvashia, Mordovia, Tatarstan, Samara, Nizhny Novgorod, Ulyanovsk and Penza Regions) from 1978 to 2021. Visual and acoustic methods were used to study the species composition during field studies. In total, 5065 birdoccurrences belonging to 157 species, 48 families and 19 orders were registered. All occurrences have a geographical reference. The large volume of data collected, the wide geographical coverage and the long-term nature of the observations determined the value of their inclusion in the GBIF and the need for publication in the Biodiversity Data Journal.We are publishing our original data on the coordinates of bird occurrences in the Middle Volga Region for the first time. Most of the original information about bird occurrences was contained in field diaries and was not available to a wide range of researchers. All 5065 occurrences are new to GBIF.